ANALYSIS OF VALUE ADDED TAX ACCOUNTING TREATMENT IN THE PRESENTATION OF FINANCIAL STATEMENTS CV. ITS BACK TO NATURE - Bonari Pardomuan Pohan (Proceeding International Seminar of Islamic Studies, 2022)
This study generally aims to evaluate the application of value added tax accounting for the presentation of financial statements in CV. ITS Back To Nature. The method used is descriptive quantitative method. And the analysis technique is used to evaluate and produce quantitative data evaluating the VAT accounting treatment. The research conducted shows the value added tax accounting treatment of CV. ITS Back To Nature applied is VAT Credit starting from crediting input VAT from purchasing raw materials to spending VAT on product sales, which is known as the credit method. Regarding the issue of input tax which cannot be compensated for by VAT on output, the Company has kept the books in accordance with financial accounting principles which are treated as raw material costs which have an impact on the decline in the company's gross profit. From the results of the analysis on the CV. ITS Back To Nature the accounting treatment of VAT is in accordance with the Value Added Tax Law no. 42 of 2009.